SISTEM INOVATIF PENCARIAN WISATA YOGYAKARTA DENGAN PELAYANAN LOKASI BERBASIS MOBILE - Risna tri prasetiyo; Anna Dina Khalifia (Politeknik Bisnis Indonesia, 2023)
This research introduces an innovative Android-based tourism search application that utilizes location-based services (LBS) through the Google Maps API. Yogyakarta, as a popular tourist destination, often faces challenges in accessing attractions outside the city center. The primary objective of this application is to provide comprehensive information about tourist attractions, assisting travelers in discovering attractions based on their preferences and categorizing them by type and the number of visitors. The research adopts a structured development approach using the Waterfall model and various Android-based programming algorithms. Despite a significant increase in the number of foreign tourists visiting Indonesia, there has been a decline in the number of domestic tourists exploring Yogyakarta, primarily due to difficulties in accessing information scattered across various platforms. The main goal of this research is to develop a mobile application that helps tourists find tourist attractions in Yogyakarta, especially those located outside the city center. The application offers a user-friendly interface, enabling users to access in-depth information about tourism categories, directions, and other essential details. Although some issues need to be addressed after the trials, this mobile tourism search application has substantial potential to support the tourism industry by providing comprehensive information to users, simplifying travel planning, and promoting lesser-known attractions.